Retinopathy and vision-related quality of life in blood dyscrasias - Lipa Mohanty; Appurv Kachhwaha; Alokit Sharma (Indian Journal of Ophthalmology)
Purpose: To study the association of retinopathy with vision-related quality of life in patients with blood dyscrasias. Settings and Design: A cross-sectional observational study was conducted at a university-based hospital. Methods: Two hundred patients with blood dyscrasias underwent comprehensive ocular examination, including dilated fundus examination. Vision-related quality of life was assessed using the National Eye Institute Visual Functioning Questionnaire-25 (NEI-VFQ-25). Results: Retinopathy was observed in 99 out of 200 patients (49.50%) with blood dyscrasias. The most common retinal findings were venous tortuosity with dilation (31.70%), intraretinal hemorrhages (27.88%), soft exudates (12.50%), white-centered hemorrhages (12.50%), and arteriolar attenuation (12.50%). A significant association was found between retinopathy in blood dyscrasias and NEI-VFQ subscales of general vision (P value: 0.01**), near activities (P value: 0.04*), distance activities (P value: 0.01**), mental health (P value: 0.01**), color vision (P value: 0.01**), peripheral vision (P value: 0.01**), role difficulties (P value: 0.01**), and social functioning (P value: 0.01**). Conclusion: The study highlights the prevalence of retinopathy in blood dyscrasia patients and its detrimental impact on vision-related quality of life. Regular fundus examinations are imperative for early detection and management of retinopathy to prevent significant visual impairment. Further research is warranted to elucidate underlying mechanisms and improve clinical management strategies.